Cu(OTf)2-Catalyzed Beckmann Rearrangement of Ketones Using Hydroxylamine-O-sulfonic Acid (HOSA) - Munnuri, Sailu; Verma, Saumya; Chandra, Dinesh; Anugu, Raghunath Reddy; Falck, John R.; Jat, Jawahar L. (Synthesis, 2019)
The Beckmann rearrangement (BKR) of ketones to secondary amides often requires harsh reaction conditions that limit its practicality and scope. Herein, the Cu(OTf)2-catalyzed BKR of ketones under mild reaction conditions using hydroxylamine-O-sulfonic acid (HOSA), a commercial water soluble aminating agent, is described. This method is compatible with most functional groups and directly provides the desired amides in good to excellent yields.
Keywords: hydroxylamine-O-sulfonic acid (HOSA); ketone; Beckmann rearrangement; Cu(OTf)2; secondary amide